Changes in the Htp-dj-nsw Formula in the Late Middle Kingdom and the Second Intermediate Period - Ilin-Tomich, Alexander (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
The paper focuses on the formal criteria to date the inscriptions currently attributed to the “Late Middle Kingdom” more precisely. This time-span is divided into three periods: the late Twelfth dynasty (Senwosret III to Neferusobek), the Thirteenth dynasty and the Second Intermediate Period. On the basis of a study of the offering formulas on 479 datable monuments, the existing dating criteria are reviewed and new approaches are established. An early date of the king Awibre Hor proposed by S. Aufrère is also disputed.